STUDY ON CALCULATIONS OF MESHING STIFFNESS OF GEAR TEETH OF PLANETARY GEAR REDUCER OF LESS TOOTH DIFFERENCE WITH BIASING CRANKSHAFT BASED ON MATLAB - XU Qiang; XU ZeYin; ZHU AiHua (Jixie qiangdu)
To calculate the different meshing points stiffness of the internal gear pairs of planetary gear reducer of less tooth difference with biasing crankshaft,the parameter and engagement angle equation of the internal and external tooth of the reducer is established; the tooth is regarded as a cantilever beam with variable sections,the numerical model used to calculate the different deformation of the tooth is built respectively,and adopts the differential quadrature method when calculating the bending and shear deformations of the variable section beams,the Matlab program to compute the different meshing points stiffness is also compiled,the method is verified with living example and experiment. The results show that this method is accurate and quick,and provide an important theoretical basis for the further study on the vibration and the maximum carrying capacity of the reducer.